Sinergitas law enforcement keimigrasian dalam kasus pelanggaran aturan adat nyepi oleh orang asing asal Polandia - Putri, Putu Triska Arintia Permata; Resen, Putu Titah Kawitri (Ex Aequo Et Bono Journal Of Law, 2024)
Tourist visits in Indonesia have increased since the issuance of various government regulations to improve the community's economy after the COVID-19 pandemic. On the other hand, the massive increase in foreign tourist visits also has negative impacts, such as increasing the risk of crime and violations. Based on the report on the number of immigration administrative actions issued by the TPI Denpasar Class I Immigration Office, there has been an increase in the number of immigration administrative actions in the form of deportation and detention of foreigners in immigration detention centers from 2020 to 2022. One of these cases of violation is the violation of the Nyepi customary rules carried out by Polish foreigners who were handled by the TPI Denpasar Class I Immigration Office together with the Sukawati Police Headquarters. This type of research is qualitative, with data taken from interviews and literature studies. This research produced several findings, namely: 1) the role of immigration, especially the Inteldakim section, in terms of law enforcement and security; 2) law enforcement/immigration law enforcement, which is based on selective policies in the form of authority to grant sanctions in the form of immigration administrative actions, namely deportation and deterrence; and 3) immigration synergy with the Sukawati Police Headquarters in the initial stages in the form of coordination, providing recommendations, and handing over foreigners for follow-up in accordance with the Immigration Law.